Multiple positive solutions of singularly perturbed differential systems with different orders - Zhang, Xinguang; Xu, Y. (Pergamon, 2010)
In this paper, we consider the multiplicity of positive solutions for a class of singular higher-order perturbed differential systems with different orders. By employing a well-known fixed point theorem, some new existence results are given under the case where nonlinearity can be sign changing.